2013
DOI: 10.1161/atvbaha.112.300251
|View full text |Cite|
|
Sign up to set email alerts
|

Association of the miR-146a , miR-149 , miR-196a2 , and miR-499 Polymorphisms With Ischemic Stroke and Silent Brain Infarction Risk

Abstract: Objective— MicroRNAs play a role in atherosclerosis-related diseases, such as cerebrovascular or cardiovascular disease. However, the effect of miR-146a , miR-149 , miR-196a2 , and miR-499 polymorphisms on stroke and silent brain infarction (SBI) susceptibility has not been reported. Methods and Results— … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(111 citation statements)
references
References 64 publications
6
105
0
Order By: Relevance
“…Moreover, previous studies have indicated that temporal miRNA regulation may be related to the progression of ischemia in the cerebral artery (17,18). Furthermore, a recent study found a significant association between miRNA single nucleotide poly-morphisms (SNPs) and the risk of ischemic stroke (19). As has been previously reported by Edelstein et al (20), as regards the regulated function of megakaryocytopoiesis, various miRNAs play a crucial role in this process, as well as in platelet biogenesis.…”
Section: Introductionmentioning
confidence: 81%
“…Moreover, previous studies have indicated that temporal miRNA regulation may be related to the progression of ischemia in the cerebral artery (17,18). Furthermore, a recent study found a significant association between miRNA single nucleotide poly-morphisms (SNPs) and the risk of ischemic stroke (19). As has been previously reported by Edelstein et al (20), as regards the regulated function of megakaryocytopoiesis, various miRNAs play a crucial role in this process, as well as in platelet biogenesis.…”
Section: Introductionmentioning
confidence: 81%
“…The homozygous GG genotype exerted no noticeable effect on the susceptibility in this study, which might be due to the limited sample size of subjects with GG genotype (only 18.3% or 19.8% in the populations). The miR-146a C>G polymorphism has also been reported to associate with the risk of ischemic stroke (Jeon et al 2013;Huang et al 2015), which indicates that ACS or CHD may share genetic risk factors with ischemic stroke. Although rs11614913 was associated with an increased risk of ACS in the females, we found no association in the whole population.…”
Section: Discussionmentioning
confidence: 99%
“…Excitingly, the understanding of the genetic risks associated with vascular disease has expanded to include the observation that polymorphisms in microRNA genes or microRNA-binding by guest on May 11, 2018 http://atvb.ahajournals.org/ Downloaded from sites in critical protein-coding genes can contribute to pathogenesis of vascular disease. 56 Recently, Jeon et al 57 found that single nucleotide variation in the miRs-146a, -149, -196a-2, and -499 were significantly associated with stroke prevalence in a Korean population, and the authors surmise this may be because of decreased expression of inflammatory mediators, such as TNFα and CRP. Although the field of microRNAs as biomarkers is continuing to evolve, there is little doubt that their use for the prediction and diagnosis of vascular disease will be significant.…”
Section: Conclusion and Translational Considerationsmentioning
confidence: 99%